Research progress on antitumor activity of XRP44X and analogues as microtubule targeting agents - Wang, Chao; Shi, Lingyu; Yang, Shanbo; Chang, Jing; Liu, Wenjing; Zeng, Jun; Meng, Jingsen; Zhang, Renshuai; Xing, Dongming (Frontiers in Chemistry, 2023)
Cancer threatens human health and life. Therefore, it is particularly important to develop safe and effective antitumor drugs. Microtubules, the main component of cytoskeleton, play an important role in maintaining cell morphology, mitosis, and signal transduction, which are one of important targets of antitumor drug research and development. Colchicine binding site inhibitors have dual effects of inhibiting proliferation and destroying blood vessels. In recent years, a series of inhibitors targeting this target have been studied and some progress has been made. XRP44X has a novel structure and overcomes some disadvantages of traditional inhibitors. It is also a multifunctional molecule that regulates not only the function of tubulin but also a variety of biological pathways. Therefore, the structure, synthesis, structure-activity relationship, and biological activity of XRP44X analogues reported in recent years were summarized in this paper, to provide a useful reference for the rational design of efficient colchicine binding site inhibitors.